Rehabilitation of aphasia: application of melodic-rhythmic therapy to Italian language - Cortese, Maria Daniela; Riganello, Francesco; Arcuri, Francesco; Pignataro, Luigina Maria; Buglione, Iolanda (Frontiers in Human Neuroscience, 2015)
Aphasia is a complex disorder, frequent after stroke (~38%), with a detailed pathophysiological characterization. Proper approaches are mandatory to devise an efficient rehabilitative strategy, in order to address the everyday life and professional disability. Several rehabilitative procedures are based on psycholinguistic, cognitive, psychosocial or pragmatic approaches, among these with neurobehavioral ratio, the Melodic Intonation Therapy (MIT) .Van Eeckhout’s adaptation to the French language (Melodic-Rhythmic Therapy: MRT) has implemented the training strategy by adding a rhythmic structure reproducing the French prosody. Purposes of this study were to adapt the MRT rehabilitation procedures to the Italian language and to verify its efficacy in a group of 6 chronic patients (5 males) with severe non-fluent aphasia and without specific aphasic treatments at least from 9 months. The patients were treated 4 days a week for 16 weeks, with sessions of 30-40 min. They were assessed 6 months after the end of the treatment (follow-up). The patients showed a significant improvement at the Aachener Aphasie Test in different fields of spontaneous speech, with superimposable results at the follow-up. Albeit preliminary, these findings support the use of MRT in the rehabilitation after stroke. Specifically, MRT seems to benefit from its stronger structure than the available stimulation-facilitation procedures and allows a better quantification of the rehabilitation efficacy.